A Novel Manipulation for Implementing Logic Operations Based on Plasmonic Resonators - Junxiong Chai; Yiyuan Xie; Yichen Ye; Lixia Fu; Lili Li; Ye Su; Ying Xiao; Yong Liu (IEEE Photonics Journal, 2019)
In this paper, a plasmonic logic device with the novel manipulation method is proposed. It consists of a hexagonal resonator in the center of the structure and dual rectangular resonators in which two sliders are embedded. The input states of the logic gate are represented by the positions of the slider. The temporal coupled-mode theory demonstrates that different positions of the slider lead to changes in the transmission spectra, which is the main idea in achieving logic operation. Ultimately, three logic operations (AND, XOR, and NOR) can be implemented simultaneously by moving the sliders and the finite-difference time-domain method is used for numerical validation. In addition, the influence of structural parameters on transmission characteristics and contrast ratio is also investigated. This paper is of great significance to the design of optical logic device on-chip and provides a new method for designing other integrated photonic devices.